Transformasi Profesional Guru Pendidikan Anak Usia Dini di Era Society 5.0 - WIDIA ASTUTI; Muhammad Azhar Gunawan (Jurnal Kajian Anak (J-Sanak), 2026)
The advancement of technology in the Society 5.0 era positions Early Childhood Education (PAUD) teachers to develop digital literacy while maintaining humanistic pedagogical principles. This study employed a descriptive qualitative method to explore digital literacy, humanistic pedagogy practices, and technology integration among PAUD teachers in Yogyakarta. Data were collected through semi-structured interviews, participant observation, and document analysis, and were analyzed using data reduction, presentation, and triangulation verification. The results indicate variations in teachers’ digital literacy: 25% low, 41.7% moderate, and 33.3% high, affecting the integration of technology in learning. Teachers with low literacy tend to use digital media operationally, while those with high literacy support interactive and project-based learning. The analysis highlights the need for continuous digital literacy training balanced with humanistic pedagogy as a foundation for teacher competence development. contributes both practically and theoretically to enhancing the quality of safe, meaningful, and adaptive early childhood education in the Society 5.0 era.